Basic Capital of Creative Economy: The Role of Intellectual, Social, Cultural, and Institutional Capital - Abu Muna Almaududi Ausat; Tareq Al Bana; Silvy Sondari Gadzali (Apollo: Journal of Tourism and Business, 2023)
In recent years, the creative economy's vital role in riding the wave of economic recovery caused by the pandemic has come to the fore. As a result, lawmakers and regulators are focusing on revitalizing the creative economy through initiatives like the online marketplace. However, the public still lacks understanding of the creative economy and what is the basic capital for the development of the creative economy. This research aims to explain the answers to the ignorance above in full. Thus, it can be used as a basis for decision making to contribute to the creative economy. This research is qualitative. Data collection techniques include listening and recording important information to conduct data analysis through data reduction, data display, and conclusion drawing. The study arrived at the conclusion that the creative economy is a concept that aims to achieve sustainable economic development based on creativity. Human capital, social capital, cultural capital, and structural institutional capital are the four types of capital that form the foundation of the creative economy. These results are expected to be an insight for the community to be more sensitive to opportunities in modern times. Because, one of the goals of the creative economy is not only to increase GDP, but also to create jobs.